Efficacy and safety of iguratimod in the treatment of rheumatic and autoimmune diseases: a meta-analysis and systematic review of 84 randomized controlled trials - Liuting Zeng; Qi He; Ying Deng; Yuwei Li; Junpeng Chen; Kailin Yang; Yanfang Luo; Anqi Ge; Xiaofei Zhu; Zhiyong Long; Lingyun Sun; Lingyun Sun (Frontiers Media S.A., 2023)
Objective: To evaluate efficacy and safety of iguratimod (IGU) in the treatment of rheumatic and autoimmune diseases.Methods: Databases such as Pubmed, Embase, Sinomed were searched (as of July 2022) to collect randomized controlled trials (RCTs) of IGU in the treatment of rheumatic and autoimmune diseases. Two researchers independently screened the literature, extracted data, assessed the risk of bias of the included literature, and performed meta-analysis using RevMan 5.4 software.Results: A total of 84 RCTs and 4 types of rheumatic and autoimmune diseases [rheumatoid arthritis (RA), ankylosing spondylitis (AS), primary Sjögren's syndrome (PSS) and Autoimmune disease with interstitial pneumonia]. Forty-three RCTs reported RA and showed that IGU + MTX therapy can improve ACR20 (RR 1.45 [1.14, 1.84], p = 0.003), ACR50 (RR 1.80 [1.43, 2.26], p < 0.0000), ACR70 (RR 1.84 [1.27, 2.67], p = 0.001), DAS28 (WMD −1.11 [−1.69, −0.52], p = 0.0002), reduce ESR (WMD −11.05 [−14.58, −7.51], p < 0.00001), CRP (SMD −1.52 [−2.02, −1.02], p < 0.00001), RF (SMD −1.65 [−2.48, −0.82], p < 0.0001), and have a lower incidence of adverse events (RR 0.84 [0.78, 0.91], p < 0.00001) than the control group. Nine RCTs reported AS and showed that IGU can decrease the BASDAI score (SMD −1.62 [−2.20, −1.05], p < 0.00001), BASFI score (WMD −1.07 [−1.39, −0.75], p < 0.00001), VAS (WMD −2.01 [−2.83, −1.19], p < 0.00001), inflammation levels (decreasing ESR, CRP and TNF-α). Thirty-two RCTs reported PSS and showed that IGU can reduce the ESSPRI score (IGU + other therapy group: WMD −1.71 [−2.44, −0.98], p < 0.00001; IGU only group: WMD −2.10 [−2.40, −1.81], p < 0.00001) and ESSDAI score (IGU + other therapy group: WMD −1.62 [−2.30, −0.94], p < 0.00001; IGU only group: WMD −1.51 [−1.65, −1.37], p < 0.00001), inhibit the inflammation factors (reduce ESR, CRP and RF) and increase Schirmer's test score (IGU + other therapy group: WMD 2.18 [1.76, 2.59], p < 0.00001; IGU only group: WMD 1.55 [0.35, 2.75], p = 0.01); The incidence of adverse events in IGU group was also lower than that in control group (IGU only group: RR 0.66 [0.48, 0.98], p = 0.01). Three RCTs reported Autoimmune disease with interstitial pneumonia and showed that IGU may improve lung function.Conclusion: Based on current evidence, IGU may be a safe and effective therapy for RA, AS, PSS and autoimmune diseases with interstitial pneumonia.Systematic Review Registration: (CRD42021289489).